Rooting of Air Layered Shoots of Quercus glauca Thunb. and Subsequent Performance of such Plants and Seedlings under Different Micro Climatic Conditions - Purohit, Vijay K.; Palni, Lok Man S.; Rikhari, Hem C.; Nandi, Shyamal K. (Indian Forester, 2005)
The rooting ability of air layered shoots of Quercus glauca, a difficult to root species, and subsequent performance of well rooted shoots under different microclimatic conditions have been examined. Different concentrations of auxins (lBA, NAA and IAA), Shuttedex and Bavistin (Carbendazim 50%) were used to induce rooting in shoots during rainy season. A relatively lower concentration of IBA (100 ppm) resulted in maximum (73.3%) rooting of air layered shoots, whereas highest number of roots per air layered shoot were formed when the same concentration of NAA was used. The survival of rooted shoots (plants) thus obtained was 100% inside a mist chamber, following transfer to soil. The increment in height and leaf number after one year was found to be maximum for plants kept inside a poly house, followed by those kept in a polypit. However, the lowest values for these two parameters were observed for plants kept in the open and under a chhappar (thatch), respectively. On the other hand maximum and minimum height increment for seed raised plants was observed when the seedlings were grown inside a polypit and in the open, respectively. Although the relative growth rate of both seedlings and air-layered plants was found to significantly differ under different microclimatic conditions, the same was not statistically different for the plants raised by these two methods, indicating that the performance of air layered plants and seedlings is comparable.